On the ambiguity of mechanical power - V. D. Pavlov (Advanced Engineering Research, 2022)
Introduction. Mechanical vibrations are widespread in the production processes. The drives of machines and mechanisms are mainly electromechanical, so mechanical reactive power is transformed into electrical reactive power of the network, impairing the quality of electricity. This explains the significance of considering the mechanical reactive power, and, as a consequence, the urgency of the presented study. The research objective is to detail the types of mechanical power under harmonic vibrations.Materials and Methods. The literature on the issues of dynamics, kinematics, vibrations, transformation of motion in oscillatory systems, etc., has been studied. Theoretical, mainly mathematical methods of research are used.Results. The powers developed under elastic deformations, forced harmonic vibrations of an inert body, and vibrations associated with gravitational influence, as well as reactive, active, full powers in the complex formulation, and mechanical powers in the vector representation are mathematically interpreted.Discussion and Conclusions. Under the mechanical harmonic vibrations, along with the sign-positive thermal power, sign-variable reactive powers develop, characterizing the reversibility of kinetic and potential energies. The total mechanical power satisfies the Pythagorean formula. The concept of mechanical reactive, active, and total powers generalizes the corresponding concepts of power from electrical engineering, and thus manifesting electromechanical dualism.